Hospital responses to the introduction of reimbursements by treatment intensity in a (presumably lump sum) DRG system - Matthias Bäuml; Christian Kümpel (University of Hamburg, Hamburg Center for Health Economics (HCHE), 2020)
Many OECD countries have replaced per-diem hospital reimbursement with lump sum payments by diagnosis-related groups (DRGs). However, modern DRG systems still allow hospitals to pass on actual treatment costs to payers, which might hinder the efficiency of health care provision. This paper analyzes hospital responses to a large-scale refinement of reimbursement practices in Germany on January 1, 2006, in which regulating authorities introduce reimbursements by treatment intensity in the market for stroke disorder. We find that the share of admissions receiving high-intensity treatment jumps by approximately 7 percentage points around the turn of the year. At the same time, a decrease in the average clinical appropriateness for patients receiving this high-intensity treatment reveals that the marginal high-intensity treated patient in 2006 is less appropriate for high-intensity treatment compared to 2005. We do not find accompanying (short-term) changes in the quality of care, such as decreases in in-hospital mortality. Thus, regulating authorities may improve efficiency by reducing the importance of extra reimbursements for marginal treatments in modern DRG systems.
Keywords: 330